MANAJEMEN KEUANGAN SEKOLAH DALAM PENGELOLAAN DANA PENDIDIKAN: STUDI KUALITATIF MELALUI OBSERVASI DI SD LABSCHOOL UNESA 2 - Hanik Halimatus Saleha; Aulia Ramadhani; Vina Cahaya Putri; Anggita Rahmadiana; Azkiya Nur Fathin; Tiana Albania Imama; Ima Widiyanah (STKIP Subang, 2026)
This study examines school financial management in managing educational funds at SD Labschool UNESA 2 using a qualitative approach through observation, interviews, and documentation. The research aims to analyze the planning, implementation, supervision, and evaluation of educational fund management. The findings show that financial management at SD Labschool UNESA 2 has been implemented systematically through planning, organizing, actuating, and controlling stages. The planning process involves the principal, treasurers, teachers, and school committees in preparing the School Activity and Budget Plan (RKAS). Financial implementation is carried out according to the planned budget allocation and supported by a transparent financial system. In addition, supervision and evaluation are conducted routinely through internal monitoring and external oversight to ensure accountability and transparency. Overall, the financial management system has supported the effectiveness of educational activities and improved the quality of school management.